Does trade integration reorient income inequality? Evidence from the post-soviet countries / M. Mesut Badur and Kazi Sohag - Badur, M. Mesut; Sohag, Kazi (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
The transition of the post-Soviet countries from the command to the market economic system cropped many social classes through a skew distribution of economic prosperity. We investigated the role of trade integration to explain income inequality for twelve post-Soviet countries for the years 1991- 2019. Given the considerable heterogeneity across the countries, time, and reverse causality, we apply a novel method, namely Quantiles via Moments approach. Our empirical findings revealed that trade integration reduced income inequality under all quantiles monotonically by promoting market competitiveness considering different economic circumstances. Precisely, the impact of trade integration was more profound at the lower quantiles while it is moderate at the middle quantiles. We also observed that economic growth and income inequality followed an inverted U-shaped relation. Besides, the reduction in government spending widened the gap between rich and poor implying an increase in income inequality. Our empirical findings reinforce the importance of trade integration to reduce income disparity by enhancing competitive market internationally. Moreover, efficient government spending and tax policy should be designed in a way that can augment the income of the middle and lower classes.